2018
DOI: 10.1039/c8dt04128h
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic silica@aqueous miscible organic-layered double hydroxide hybrids

Abstract: We present the synthesis of a series of dendritic hierarchical hybrid SiO2@AMO-LDHs with tuneable properties suitable for a wide range of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…35 Typically, they have been synthesized by a conventional co-precipitation method, which normally produces materials with stone-like morphologies due to the high degree of platelet aggregation. 33,34 In addition, O'Hare et al have developed a highly dispersed LDHs on SiO 2 or zeolite surfaces obtained by AMOST in which the AMO solvents such as acetone and ethanol replace the surface-bound water inside the interlayer of LDHs, resulting in an exfoliation of the layers, eventually giving uniform flower-like or nanosheet morphologies of LDH highly dispersed on the surface of porous solid supports. 33,34 To date, zeolites with hierarchical porous structures containing both microporous and mesoporous structures have been broadly used in a catalytic application because they can improve accessibility of the bulky reagent molecules to catalytic active centers and diffusion limitation due to the shortened path length of crystals, leading to minimizing the catalyst deactivation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Typically, they have been synthesized by a conventional co-precipitation method, which normally produces materials with stone-like morphologies due to the high degree of platelet aggregation. 33,34 In addition, O'Hare et al have developed a highly dispersed LDHs on SiO 2 or zeolite surfaces obtained by AMOST in which the AMO solvents such as acetone and ethanol replace the surface-bound water inside the interlayer of LDHs, resulting in an exfoliation of the layers, eventually giving uniform flower-like or nanosheet morphologies of LDH highly dispersed on the surface of porous solid supports. 33,34 To date, zeolites with hierarchical porous structures containing both microporous and mesoporous structures have been broadly used in a catalytic application because they can improve accessibility of the bulky reagent molecules to catalytic active centers and diffusion limitation due to the shortened path length of crystals, leading to minimizing the catalyst deactivation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Metals loaded on zeolites are utilized as highly efficient catalysts for the synthesis of CNTs because zeolites have well-defined porous structures and high surface areas providing the highly dispersed metal active sites, resulting in high yields of CNTs and narrow distributed tube diameters. , Recently, layered double hydroxide (LDHs)/zeolite composites synthesized via an aqueous miscible organic solvent treatment (AMOST) process have been illustrated as an efficient method to produce highly dispersed metal nanoparticles on zeolite surfaces. Generally, LDHs are layered clay minerals consisting of positively charged layers and interlayer anions. They are generally represented by the chemical formula [M 2+ 1– x M 3+ x (OH) 2 ]­[A n – ] x / n · z H 2 O, where M 2+ and M 3+ are divalent cations (e.g., Mg 2+ or Ni 2+ ) and trivalent cations (e.g., Al 3+ , Fe 3+ , or Cr 3+ ), respectively, A n – is an interlayer anion (e.g., CO 3 2– or Cl – ), and z is the amount of water .…”
Section: Introductionmentioning
confidence: 99%
“…Although it has not been clearly reported, one will agree that the main purpose of the washing of LDH is to discard the unreacted products after the reaction has been completed. However, Dermot O’Hare et al proved for the first time that a post treatment of LDHs through a precise procedure using an appropriate aqueous miscible organic solvent can increase the specific surface area and alter the crystallinity, morphology, and thermal behaviour of the final products [ 26 , 27 , 28 , 29 ]. Consequently, Ziling Wang et al post-treated NiAl-LDH using ethanol following the reported procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] It is well-known that a cascade reaction is sequentially carried out with two or multiple individual reactions within a one-pot system, [3] in which the complicated processes, such as product separation, purification, costs of solvents, and chemicals, and the production of pollutants have their structure from stone-like morphology obtained in conventional LDHs to flower-like or nanosheet structure because the AMO solvent such as acetone and ethanol can replace the surface-bound water inside the interlayer, resulting in an easy dispersion and exfoliation of their structures. [22,23] Therefore, the modified LDHs obtained via AMOST (AMO-LDHs) exhibit excellent textural properties, such as good dispersibility, and high surface area with respect to the conventional LDHs. [24,25] As mentioned above, by integrating the beneficial aspects of FAU zeolite and AMO-LDHs as acid and basic catalysts, respectively, it is an interesting choice to achieve high catalytic performance on an acid-base cascade reaction.…”
Section: Introductionmentioning
confidence: 99%